Prediction of creep crack initiation in Cr–Mo–V steel specimens with different geometries. (2nd January 2017) - He, J. Z.; Wang, G. Z.; Tu, S. T.; Xuan, F. Z.
Abstract: By using stress dependent creep ductility and strain rate model in a ductility exhaustion based damage model, the creep crack initiation (CCI) behaviour in Cr–Mo–V steel specimens with different geometries and dimensions (different constraints) over a wide range of C * has been predicted by finite element simulations. The predicted creep crack initiation time agree well with the existing experimental data. In low and transition C * regions, the constraint induced by specimen geometries and dimensions has obvious influence on CCI time. With increasing constraint level of specimens, the CCI time decreases due to the increase of stress triaxiality ahead of crack tip. Different CCI trends and constraint effects on CCI behaviour in a wide range of C * result from the interaction of crack-tip stress state and stress dependent creep ductility of the steel. It is suggested that in CCI life assessments of high temperature components, the long-term CCI time data at low C * region should be obtained and used, and the constraint effects need to be considered by using constraint dependent CCI data.